Analisa Perhitungan Specific Water Consumption Pada Pembangkit Listrik Tenaga Air Di Sistem Minahasa - Peils Y. Tangkilisan; Hans Tumaliang; Sartje Silimang (Jurnal Teknik Elektro dan Komputer, 2015)
Abstrack-- Minahasa electrical power system has an installed capacity of 340,65 MW. However, the power capacity is only 288,62 MW. Power generating system consists of two sub-systems, namely thermal sub-systems and hydro sub-systems. Thermal sub-system has a capacity of 235.32 MW that is much larger than the hydro sub-system that is 53.3 MW. Therefore, the cost of plant operations to be very expensive because of fuel consumption of thermal power plant to be very much. Input-output characteristics of hydroelectric power generation illustrates the relationship between the inputs to the prime movers (turbines) in the form of the amount of water that flowed between the blades of the turbine equation of time with the power output of the generator. The output of the hydro power plant is a power that is sent out is reduced by the net generator output power for its own use such as for pumps, battery charging and other supporting equipment. By knowing the value of specific water consumption (SWC) and the electric energy generated, the water flow can be determined. This method is very efficient because it has a record of hydropower energy generated each day. Accordingly, if desired length of water discharge data, this can be done for hydropower also has a note of the power / energy generated during it. At one hydropower, SWC value will depend on the value of the head, and the efficiency of equipment used (in particular the efficiency of the turbine and generator efficiency). In the calculation of Specific Water Consumption (SWC) is influenced by two things, first by the amount of water flow per day, per month and per year, both by the average number of loads perday,permonthandperyear.At Tonsea Lama hydropowerplant we can know the SWC in 2014 through an average yield of water consumption by 25,049,419,742 M3 and the average Energy of 557,552,813 kWh and SWC amounted 4.49 M3/kWh. At Hydro powerplant Tanggari 1 then we can know the SWC in 2014 through an average yield of water consumption amounted to 17,941,035 M3 and the average Energy of 9,133,881kWh and SWC amounted to1.96M3/kWh. At Hydropowerplant  Tanggari 2 we can know the SWC in 2014 through an average yield of 19,705,698M3 water consumption and the average Energy of 7,780,368 kWh and SWC at 2.53 M3/ kWh. Keyword : Energy,input-output characteristics, Specific water consumption, water consumption,. Abstrak-- Sistem tenaga listrik Minahasa mempunyai kapasitas terpasang 340,65 MW, namun daya mampu hanya 288,62 MW. Sistem pembangkit terbagi dua yaitu sub sistem hidro dan sub sistem termal. Sub sistem termal mempunyai kapasitas daya mampu 235,32 MW yang jauh lebih besar dari sub sistem hidro yaitu 53,3 MW. Oleh karena itu, biaya operasi pembangkit menjadi sangat mahal karena pemakaian bahan bakar dari pembangkit termal sangat banyak. Karateristik input-output dari pembangkit tenaga listrik hidro menggambarkan hubungan antara input ke penggerak mula (turbin) berupa jumlah air yang dialirkan diantara sudu-sudu turbin persamaan waktu dengan output daya dari generator. Output dari pembangkit listrik hidro adalah daya yang dikirim keluar yaitu net output generator dikurangi dengan daya untuk pemakaian sendiri seperti untuk pompa, pengisian baterai dan peralatan penunjang lainnya Dengan mengetahui nilai specific water consumption (SWC)  dan energi listrik yang dihasilkan, maka debit air dapat ditentukan. Metoda ini sangat efisien karena PLTA mempunyai catatan data energi yang dibangkitkan tiap harinya. Dengan demikian, jika diinginkan data debit air yang panjang, hal ini bisa dilakukan selama PLTA juga mempunyai catatan mengenai daya/energi yang dihasilkan selama itu. Pada suatu PLTA, nilai swc akan sangat bergantung pada nilai head, dan efisiensi peralatan yang dipergunakan (khususnya efisiensi turbin dan efisiensi generator). Dalam perhitungan Specific Water Consumption(SWC) dipengaruhi oleh dua hal, pertama oleh jumlah debit air perhari, perbulan dan pertahun, kedua oleh jumlah beban rata-rata perhari, perbulan dan pertahun Pada PLTA Tonsea Lama  kita dapat mengetahui SWC tahun 2014 melalui hasil rata-rata pemakaian air sebesar 25049419742 M3 dan Energi rata-rata sebesar 557.552.813 kWh dan SWC sebesar 4.49 M3/kWh. Pada PLTA Tanggari 1 maka kita dapat mengetahui SWC tahun 2014 melalui hasil rata-rata pemakaian air sebesar 17,941,035 M3 dan Energi rata-rata sebesar 9,133,881kWh dan SWC sebesar 1.96 M3/kWh. Pada PLTA Tanggari 2 kita dapat mengetahui SWC tahun 2014 melalui hasil rata-rata pemakaian air sebesar 19,705,698M3 dan Energi  rata-rata sebesar 7,780,368 kWh dan SWC sebesar 2.53 M3/kWh. Kata Kunci : Energy,input-output characteristics,Pemakaianair, Specific water consumption.